The Correlation Between Pharmacological Rationality and Therapeutic Outcomes in Patients with Gout at RSI Siti Khadijah Palembang - Rennie Puspa Novita; Annisa Amriani; Vitri Agustiarini; Fitriya Fitriya; Selly Septi Fandinata; Norma Nisya (Jurnal Kefarmasian Indonesia, 2025)
Gout is a kind of arthritis characterized by the presence of elevated amounts of uric acid in the bloodstream (hyperuricemia), leading to the accumulation of monosodium urate (MSU) crystals within the joints. The appropriate utilization of medications in individuals with gout can significantly impact the efficacy of treatment. The objective of this study is to establish a correlation between pharmacological rationality and therapeutic outcomes among gout patients at RSI Siti Khadijah Palembang from January 2020 to December 2022. The present work employs an observational analytic approach, utilizing cross-sectional and cohort study designs. The data were collected retrospectively by the utilization of the total sampling approach, encompassing a complete sample size of 32 patients. The utilization of rationality drugs yielded a 100% accuracy rate in terms of diagnosis, indication, patient selection for urate-lowering therapy, and 93.55% for analgesic anti-inflammatory treatment patient. The correct drug was administered in 100% of cases, while the appropriate dosage for urate-lowering therapy was achieved in 90.625% of instances and 100% for analgesic anti-inflammatory treatment. The route and timing of drug administration were both executed correctly in 100% of cases, and a high level of vigilance for potential side effects was maintained at 100% accuracy. The findings from Fisher's exact test demonstrated a statistically significant association between the effectiveness of urate-lowering medication and analgesic anti-inflammatory treatment in terms of obtaining normal uric acid levels (p<0.05) and reducing pain levels in individuals with gout (p<0.05). The judicious utilization of pharmaceutical substances is a viable approach for attaining desired therapeutic outcomes.